Virtual global health: the perceptions of students and practitioners of healthcare professions in Sudan on the project ECHO telementorship program– a US academic institution collaborative - Insaf Omar; Hadeel Abdelseid; Abrar Abdelrahim; Ana Carolina Barbosa de Lima; Lana Ismail; Marah AbdelMotalab; Reem Ahmed; Nada Fadul (BMC Medical Education)
Abstract Background The COVID-19 pandemic has exposed healthcare system vulnerabilities in low- and middle-income countries, including Sudan. The Community Medical Response Team (CMRT) was established to combat the spread of COVID-19 through collaboration with a US-based Project Extension for Community Healthcare Outcomes (ECHO) telementorship, empowering Sudanese healthcare workers with vital knowledge and skills. This study aims to describe the CMRT ECHO program, evaluate participant satisfaction, gauge knowledge enhancement, and reflect on correlations between attendance frequency and participant profession. Methods Data was collected from virtual telementorship sessions provided from December 2021 to March 2023 using the University of Nebraska Medical Center Project ECHO hub. Post-session confidential online surveys were used to assess participants’ profession, satisfaction, self-reported knowledge increase, and practice changes. Wilcoxon rank sum test and chi-square test were used to identify associations between attendance frequency, professional category, and various outcomes. Results Analysis of 2,667 survey responses across 42 sessions revealed 880 unique participants, including 466 (53%) medical doctors, 152 (17%) public health staff, and 262 (30%) other clinical personnel. The average attendance per session was 64 participants and the mean frequency of attendance was 3 sessions. Participants reported a significant increase in knowledge after sessions (p < 0.0001). Noteworthy findings include high session relevance (71%), willingness to recommend the sessions (80%), and application of learned knowledge (85%). Medical doctors reported the highest knowledge increase (p < 0.001), session relevance (p < 0.001), looking up additional information (p < 0.001), and sharing with colleagues (p < 0.001). Other clinical personnel were more likely to recommend sessions to colleagues (p < 0.001) and change how they work with patients/community members (p = 0.01). Positive correlations were observed between attendance frequency and both knowledge increase (p < 0.001) and application in practice (p < 0.001). Conclusions The CMRT ECHO program has proven to be relevant and effective for diverse healthcare professionals, enhancing the understanding of COVID-19-related knowledge in Sudan, and showcasing the potential of virtual telementorship in low- and middle- income countries. The study highlights varying impacts across professions and positive outcomes linked to attendance, underscoring the value of tailored educational interventions in global health crises.